Cultures of governance and peace : A comparison of EU and Indian theoretical and policy approaches - Samāddāra, Raṇabīra; Burgess, J. Peter; Richmond, Oliver P. (Book collections on Project MUSE., 2016)
This volume brings together insights which look at the intersection of governance, culture and conflict resolution in India and the European Union.